Piezoaeroelastic analysis and characterization of two-degree-of-freedom systems with multi-segmented nonlinearities - Bouma, A.; Le, E.; Vasconcellos, R. [UNESP]; Abdelkefi, A. (American Institute of Aeronautics and Astronautics (AIAA), 2022)
A two-degree of freedom piezoaeroelastic energy harvesting system with freeplay and multi-segmented nonlinearities in the pitch degree of freedom is investigated. The nonlinear governing equations of the considered aeroelastic model are derived and discussed along with the piecewise function representation of the concentrated nonlinearity, modeling of the aerodynamic loads, energy harvesting modeling, and results and conclusions are presented. The unsteady representation based on the Duhamel formulation is used to model the aerodynamic loads without the inclusion of stall effects. The nonlinear piezoaeroelastic response is carried out in the presence of multi-segmented nonlinearities before and after the onset of flutter. Such nonlinearities can be introduced to aeroelastic energy harvesters for performance enhancement through the possible existence of sudden jumps and chaotic responses due to the grazing bifurcation and the reduction of wind speed to induce self-excited motions.